Failure investigation of a secondary super heater tube in a 140 MW thermal power plant. (April 2017) - Saha, Atanu; Roy, H.
Highlights: Failure investigative study was conducted for a secondary super heater tube of a 140 MW thermal power plant. Different destructive tests including micro structural analysis were conducted to predict the cause of failure. Micro structural analysis revealed formation of creep voids and linkage of creep voids. It was observed that the tube had failed due to severe creep damage caused by high metal temperature during service. Abstract: This article describes the findings of a detailed investigation into the failure of a secondary super heater tube in a 140 MW thermal power plant. Preliminary macroscopic examinations along with visual examination, dimensional measurement and chemical analysis were carried out to deduce the probable cause of failure. In addition optical microscopy was a necessary supplement to understand the cause of failure. It was concluded that the tube had failed due to severe creep damage caused by high metal temperature during service. The probable causes of high metal temperature may be in sufficient flow of steam due to partial blockage, presence of thick oxide scale on ID surface, high flue gas temperature etc. rupture.